The world almanac and book of facts 2026 - Janssen, Sarah, 1982- (World Almanac Books, 2025)
"The World Almanac is America's bestselling reference book of all time, with more than 83 million copies sold. For more than 150 years, this compendium of information has been the authoritative source for school, library, business, and home. The 2026 edition ... reviews the biggest events of 2025 and will be your go-to source for questions on any topic in the upcoming year. Praised as a 'treasure trove of political, economic, scientific, and educational statistics and information' by The Wall Street Journal, [it] will answer all of your trivia needs"--